Grants for Income Generation - Ritchie, Anne (World Bank, Washington, DC, 2012)
Communities supported by World Bank rural development projects often cite support for the development of income-generating activities (IGAs) as a critical need. This note identifies some of the core problems encountered by Bank task teams that attempt to respond to this need, outlines the issues involved, and offers suggestions on some of the points that should be kept in mind when designing grant programs for this purpose. Specifically, this note looks at how grants can develop economic and social infrastructure, how grants can be used to acquire privately owned productive assets, and suggestions on designing such types of grants. The paper concludes with ideas on the role for grants for income generation, and how such grant programs must be carefully designed and monitored.